Evaluasi Pelatihan, Motivasi, Insentif dan Pengaruhnya pada Kinerja Karyawan - Dadan Akhmad Muharam; Burhan Nurdin (International Journal Administration, Business & Organization, 2020)
The purpose of this study is to determine the influence of training, intensive and motivation on work productivity. The data are collected through surveys, observation, and data collection. This study uses multiple linear regression analysis through the SPSS program. The employees of the company, with a total of 110 people are used as the population of the study, and 86 of them are used as the sample. The results of the study show that partially, training and motivation do not affect employees’ work productivity, while incentives have a positive and significant effect. Simultaneously, training, intensive and motivation have a positive and significant effect on employees’ work productivity